Keabsahan Pelimpahan Porsi Haji melalui Wasiat Wajibah dan Transformasi Hukumnya terhadap Hukum Islam - Ikbal, Muchamad; Mukhlas, Oyo Sunaryo; Saebeni, Beni Ahmad (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
This study discusses the discourse of fiqh al-nawāzil which is rooted in the fundamental disparity between Islamic Family Law (classical inheritance and will law) and Contemporary Law (Hajj queue regulation Law No. 8 of 2019 and fiat of the transfer of one person to the Director General of PHU No. 130 of 2020). This background raises a normative dilemma when the right to worship (al-haq al-'ibādi) is threatened with forfeiture because classical instruments clash with the principle of lā waṣiyyata li wārith and the limits of al-thuluth. The main purpose of this research is to propose a Mandatory Will as a transformative solution of Islamic Law to provide a fair and strong sharia foundation for the existing state administrative policies. The method used is Fiqh al-Nawāzil with the approach of Istislah (Maslahah Mursalah) and Qiyās Istiḥsānī, which places the portion of Hajj as an obligation that must be fulfilled (al-wājib al-waṣiyyah) equivalent to debt, so that it can methodologically neutralize the limitation of classical inheritance. The conclusion shows that the Obligatory Will has succeeded in bridging this conflict, providing a Legal Impact in the form of modernizing Islamic Family Law, and affirming the ability of Islamic Law to realize maqāṣid al-sharī'ah (ḥifẓ al-dīn and ḥifẓ al-māl) in the contemporary era. The recommendation urges that amendments to the Compilation of Islamic Law (KHI) and hajj regulations (including the strengthening of Kepdirjen 130/2020) be immediately carried out to institutionalize the Obligatory Will, accompanied by the DSN/MUI Fatwa to prevent the commercialization (tadāwul) of the hajj portion and ensure substantive justice for the heirs.